Mg doping of 3D semipolar InGaN/GaN‐based light emitting diodes. Issue 11 (14th August 2014) - Wang, Junjun; Gao, Yumin; Alam, Saiful; Scholz, Ferdinand
<x xml:space="preserve">Abstract</x> The effects of different Mg doping concentrations in the main p‐GaN layer and the p‐GaN capping layer on the electroluminescence (EL) properties of three‐dimensional semipolar InGaN/GaN light emitting diode structures grown on GaN stripes with triangular cross‐section were investigated. Secondary ion mass spectrometry analysis revealed the Mg concentration of the 3D semipolar p‐GaN, indicating a higher Mg incorporation efficiency on the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ckt2mv1" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />101¯1</alternatives> facet as compared to the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ckt2mwk" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />112¯2</alternatives> facet. The EL output power is low with a too low Mg concentration of 3 × 1019 cm−3, probably due to the inferior hole injection efficiency and stays almost constant with the Mg concentration ranging from 4 × 1019 cm−3 until 1.3 × 1020 cm−3 for the 3D LEDs with the <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh2ckt2mfd" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />101¯1</alternatives> facet. Heavy Mg doping in the p‐GaN capping layer is required to achieve good ohmic contact performance.